Bacterial contamination of mobile phones of medical laboratory workers at Sana'a city, Yemen and their antimicrobial susceptibility - Wadhah Hassan Edrees; Mohammed Sadeq Al-Awar (GarVal Editorial Ltda., 2020)
Context: Mobile phones of laboratory workers could harbor a variety of potentially pathogenic bacteria that cause nosocomial infection for the patients, self, and family members. Aims: To determine the bacterial contamination on mobile phones belonging to the medical laboratory workers and assessment the antimicrobial susceptibility patterns of isolated bacteria at Sana'a city, Yemen. Methods: A cross-sectional study was conducted from January to February 2020 on 100 laboratory workers' mobile phones, which were randomly selected by moistened sterile swabs. The data were collected by using a designed questionnaire. The collected samples were transported to the microbiology laboratory at Al-Razi University for bacteria isolation and identification by standard bacteriological procedures. Antibiotic susceptibility testing was performed by the disc diffusion methods. Results: The results revealed that the overall rate of bacterial contamination on the mobile phone was 70% with one type of pathogenic bacteria (88.6%). Staphylococcus aureus (34.6%) was the most frequently isolated bacteria followed by Staphylococcus epidermidis (23.1%), Pseudomonas sp. (20.5%), Staphylococcus saprophyticus (15.4%), Enterobacter aergene (2.5%), Escherichia coli (1.3%), Citrobacter intermedites (1.3%), and Citrobacter freundiii (1.3%). The antibiotics susceptibility tests revealed that the highest sensitivity were S. aureus, S. epidermides, and S. saprophyticus against gentamycin, Pseudomonas sp. against kanamycin, E. aergenes against all tested antibiotics, and C. intermedites against gentamycin, vancomycin, and kanamycin. Also, Pseudomonas sp. was highly resistant to cefepime and vancomycin and S. saprophyticus to cefepime. Conclusions: Mobile phones might play a role in the transmission of potentially pathogenic bacteria. It is required to promote personal hygiene and regularly disinfect the mobile phones and hands by alcohol before leaving the lab to minimize the cross-infection to the community and environment.